Female masculinisation and reverse sexual dimorphism in the North Island Brown Kiwi (Apteryx mantelli) : a study using wild and captive birds : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University, Manawatū, New Zealand - McLeod, Caitlin (Massey University, 2024)
While sexual dimorphism is widely known in birds, little is known about when it is reversed. Species with reversed sexual dimorphism and/or sex roles often have females that show masculinisation in deviation from traditionally dimorphic pathways. This study investigates the endocrine profile of both male and female North Island brown kiwi across the breeding and non-breeding season as well as captive and wild status. Analysis of these profiles reveals androstenedione as a hormone of interest in female kiwi masculinisation, as well as significant differences between the endocrine profiles of birds in captivity from those in the wild. This study also describes the courtship behaviour of pairs of brown kiwi in the wild, adding nuance to our understanding of sexual dynamics between these birds.
Figures are reproduced with permission.
Keywords: reverse sexual dimorphism; reverse sex roles; masculinisation; kiwi courtship; androstenedione; 310911 Animal structure and function; 310901 Animal behaviour